A potential therapeutic target in traditional Chinese medicine for ulcerative colitis: Macrophage polarization - Yang, Zhihua; Lin, Shanshan; Feng, Wanying; Liu, Yangxi; Song, Zhihui; Pan, Guiyun; Zhang, Yuhang; Dai, Xiangdong; Ding, Xinya; Chen, Lu; Wang, Yi (Frontiers in Pharmacology, 2022)
Intestinal macrophages are the main participants of intestinal immune homeostasis and intestinal inflammation. Under different environmental stimuli, intestinal macrophages can be polarized into classical activated pro-inflammatory phenotype (M1) and alternative activated anti-inflammatory phenotype (M2). Its different polarization state is the “guide” to promoting the development and regression of inflammation. Under normal circumstances, intestinal macrophages can protect the intestine from inflammatory damage. However, under the influence of some genetic and environmental factors, the polarization imbalance of intestinal M1/M2 macrophages will lead to the imbalance in the regulation of intestinal inflammation and transform the physiological inflammatory response into pathological intestinal injury. In UC patients, the disorder of intestinal inflammation is closely related to the imbalance of intestinal M1/M2 macrophage polarization. Therefore, restoring the balance of M1/M2 macrophage polarization may be a potentially valuable therapeutic strategy for UC. Evidence has shown that traditional Chinese medicine (TCM) has positive therapeutic effects on UC by restoring the balance of M1/M2 macrophage polarization. This review summarizes the clinical evidence of TCM for UC, the vital role of macrophage polarization in the pathophysiology of UC, and the potential mechanism of TCM regulating macrophage polarization in the treatment of UC. We hope this review may provide some new enlightenment for the clinical treatment, fundamental research, and research and development of new Chinese medicine of UC.